Subsidiary size and the level of subsidiary autonomy in multinational corporations: a quadratic model investigation of Australian subsidiaries - Johnston, Stewart; Menguc, Bulent (Journal of International Business Studies, 2007)
We investigate the relationship between subsidiary size and subsidiary autonomy in multinational corporations (MNCs) and conclude that a quadratic inverted U-shaped model is the best fit to our data. Founding our arguments in resource dependence theory, we propose that, while the subsidiary is relatively small, increasing subsidiary size will correlate with increasing resources in the subsidiary and a consequent increase in subsidiary autonomy. This positive linear relationship persists until an inflection point is reached and subsidiary autonomy begins to decline. We argue that this is due to increasing subsidiary size bringing increasing coordination complexity, a need for greater inputs of managerial experience and expertise, and growing interdependence between the subsidiary and the rest of the corporation. Employing a sample of 313 Australian subsidiaries of mostly US, UK, European and Japanese MNCs, we use a three-step hierarchical regression to investigate controls only, linear and quadratic effects of subsidiary size on subsidiary autonomy. The quadratic inverted-U model supports and extends Hedlund's (1981) proposition. A post hoc investigation suggested that there might be value in exploring a sinusoidal relationship between size and autonomy.